Characteristics of Bituminous Binders Modified with Waste Oils: Physical, Chemical, and Rheological Properties - Yalcin, Erkut; Yilmaz, Mehmet (Springer Int Publ Ag, 2022)
This study aims to investigate the effects of waste vegetable oil and waste engine oil modifications on chemical compositions, physical and rheological properties of pure bitumen. The modified binders in the study were prepared by including waste vegetable oil and waste engine oil at 7 different ratios in pure binders. To reveal the main chemical compositions of waste vegetable oil and waste engine oil, gas chromatography-mass spectrometry was used. To evaluate the physical and mechanical properties of pure binders and binders with waste oils, penetration, softening point, flash point, and force ductility tests were conducted. To determine the rheological properties of binders with waste vegetable oil and waste engine oil modifications, rotational viscometer and dynamic shear rheometer tests were conducted. Furthermore, Fourier-transform infrared spectroscopy was used to investigate the differences between the functional groups of pure binder and modified binders. In conclusion, the inclusion of waste vegetable oil and waste engine oil in pure bitumen resulted in decreases in the viscosity and softening point of asphalt mixtures while leading to increases in penetration value. Moreover, as the additive content increased, the complex modulus values were decreased in both types of mixtures. The increases in phase angle indicated that the binders had a more viscous structure. As the additive content increased in both the waste vegetable oil binder and the waste engine oil binder, the elasticity values decreased. Finally, it was determined that the deformation energy of the binders decreased with the increase of the additive content.
Keywords: Waste vegetable oil; Waste engine oil; Bitumen; Rheological properties; Modification